1980
DOI: 10.4319/lo.1980.25.4.0719
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of planktonic bacterial production in an oligotrophic lake1

Abstract: Planktonic heterotrophic bacterial production in Mirror 1,ake (New IIampshirc) was cstimated by several different methods. Production ranged between 3 and 8 g C * m 2* yr-' based on organic C fluxes and the sum of bacterial losses. The close agreement with the estimate of 6.5 * 1.8 (X ? SE) obtained by the ssSOa method (in which bacterial S uptake was multiplied by a C:S ratio of 50) supports the validity of using this method in aerobic freshwaters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
2

Year Published

1982
1982
2005
2005

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 25 publications
4
50
0
2
Order By: Relevance
“…Values in Black Creek were 15.6-525.3 mg C m-2 with a mean of 143.0. The differences in areal biomass between the two rivers were caused by differences in volumetric concentrations rather than differences in depth, which varied from < 1 to 3 m. In comparison, the mean annual standing stock of bacteria in Mirror Lake, New Hampshire, was 80 mg C mm2 (Jordan and Likens 1980: water depth 5.7 m). Bacterial biomass ranged annually from 50 to 400 mg C m-2 in Lake Mendota (Pedros-Alib and Brock 1982: water depth 24 m).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Values in Black Creek were 15.6-525.3 mg C m-2 with a mean of 143.0. The differences in areal biomass between the two rivers were caused by differences in volumetric concentrations rather than differences in depth, which varied from < 1 to 3 m. In comparison, the mean annual standing stock of bacteria in Mirror Lake, New Hampshire, was 80 mg C mm2 (Jordan and Likens 1980: water depth 5.7 m). Bacterial biomass ranged annually from 50 to 400 mg C m-2 in Lake Mendota (Pedros-Alib and Brock 1982: water depth 24 m).…”
Section: Discussionmentioning
confidence: 86%
“…Reported cell volumes for rivers range from 0.03 to 0.28 pm3 (Geesey et al 1978;Geesey and Costerton 1979;Bell et al 1983). Jordan and Likens (1980) calculated a mean volume of bacteria in Mirror Lake of 0.088 bm3. Volumes in Lake Mendota, Wisconsin, averaged 0.1 G pm3 (PedrosAlio and Brock 1982).…”
Section: Discussionmentioning
confidence: 99%
“…A conversion factor of 1.2 X 10-7 pg C pm-3 was used for calculating biomass from biovolume. This value is the median of those cited in the literature which vary in the range 0.87 to 1.65 X 10-7 (Ferguson & Rublee 1976, Williams & Carlucci 1976, Watson et al 1977, Hagstrom et al 1979, Jordan & Likens 1980, Pedros-Alio & Brock 1982.…”
Section: Methodsmentioning
confidence: 99%
“…13acterial production estimated for various aquatic systems has been in the range of 18-44% of phytoplankton primary production on an annual basis (Jordan and Likens 1980;Larsson and Hagstrom 1982;Peldros-Aho and Brock 1982;Riemann 1983;Love11 and Konopka 1985), and the review by Cole et al ( 1988) suggests an average of 30%. The fate of this production is poorly understood, but several workers have suggested that grazing by protozoans may be important (e.g.…”
Section: Acknowledgmentsmentioning
confidence: 99%